SIMULTANEOUS DETERMINATION OF AMINOTRIAZOLE AND TRIAZOLOPYRIMIDINONE - SUBSTRATE AND INTERMEDIATE IN THE SYNTHESIS OF «TRIAZIDE» BY HPLC - A. V. Baklykov; A. A. Tumashov; S. K. Kotovskaya; E. N. Ulomskiy; G. L. Rusinov; V. L. Rusinov; O. N. Chupahin; V. N. Charushin (Разработка и регистрация лекарственных средств)
Method of simultaneous determination of aminotriazole and triazolopyrimidinone using HPLC with UV-detection was developed. For best chromatographic performance Zorbax NH2 amino phase column (Agilent Technologies, USA) was selected. The applicability of the developed method for providing technological control of the 1st stage of «Triazide» production was approved according to the results of validation procedure.